A comparative analysis of cold war and post-cold war media framing of aviation disasters - Daud Isa; Steve Urbanski (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
This study builds on previous research that examined U.S. media coverage of two airline disasters – KAL007 and IR655 – during the Cold War in the 1980s. It explores new Cold War frames in The New York Times and The Moscow Times’ coverage of the downing of Malaysian Airlines Flight MH17 in 2014. Additionally, U.S. and Russian official narratives of the incident were compared to the MH17 coverage by the two selected newspapers. Results reveal an absence of hostile Cold War assertions but indicate a link between media frames and the U.S. and Russian government positions. Additionally, findings shed light on the Moscow-Washington relations against the backdrop of intense confrontation between Russia and the West not witnessed since the collapse of the Soviet Union.